Pengujian organoleptik kulit pangsit dengan penambahan bubuk tulang ayam dalam tiga konsentrasi berbeda - Michael Ricky Sondak; Alysia Belinda Santoso (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
The purpose of this research is to determine chicken bone powder can be utilized as an additional material for making wonton skin. Organoleptic test held by using three repetition with different concentration each. Organoleptic test focused on 30 different panelists to determine which sample was the best and preferred by the panelists. To collect organoleptic test data, questionnaires were distributed using a hedonic scale. This test focused on organoleptic appeal factors such as colour, aroma, taste and texture. There are 4 concentration used on this research: 0% (no addition of chicken bone powder), 10%, 20% and 30%. ANOVA used to find out which sample the panelists liked the most. Based on the ANOVA test, the wonton skin product using the most preferred chicken bone powder with a 10% addition which has the brown colour, similar aroma with general wonton skin, savoury taste and crunchy texture.